Pengaruh Influencer terhadap Keputusan Pembelian Produk WB Glow di Makassar: Peran Loyalitas Pelanggan dalam Live Streaming Facebook - Sahabuddin, Romansyah; Afifah, Rifqah; Mukrima; Wilyah, Widyanti; Arif, Hery Maulana (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research aims to explore the impact of influencers on purchasing decisions for WB Glow products via live streaming on Facebook, with customer loyalty as an intervening variable. The approach used was quantitative, with a survey involving 100 adult female WB Glow users who had watched the live streaming. The analysis results show that influencers have a positive and significant influence on purchasing decisions, while increasing customer loyalty. Additionally, loyalty is proven to mediate the relationship between influencer influence and purchasing decisions. These findings emphasize the importance of marketing strategies that utilize influencers in the current digital era, as well as the importance of building customer loyalty to increase promotional effectiveness. This research provides new insights for marketers in designing more effective and relevant campaigns in the digital marketing era.